Kualitas Website dan Harga Mempengaruhi Loyalitas Pelanggan Melalui Variabel Kepercayaan di Traveloka - Hadita Hadita (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
This study aims to find out the factors of website quality, and trust that affect customer loyalty related to purchasing airline tickets and booking hotel boldly on Traveloka. Non-probability sampling procedures and accidental sampling procedures. Questionnaires were boldly distributed to 150 informants. Path analysis data analysis technique supported by the Amos program. The results of the first hypothesis which states that the website quality variable is only able to influence the trust variable of 46.6% with a sig level value. 0.000 is lower than the standard coefficient of 0.05, then the website quality variable is said to have a direct influence on trust. The results of the second hypothesis state that the price variable is only able to influence the confidence variable of 48.7% with a sig level. 0.000 is lower than the standard coefficient, which is 0.05, which means that the variable is said to have a direct influence on trust. The results of the third hypothesis state that the website quality variable is only able to influence the customer loyalty variable by 17.8% with a sig level. as much as 0.007 is lower than the standard coefficient of 0.05, then the website quality variable is said to have a direct influence on customer loyalty. The result of the fourth hypothesis is that the value of the coefficient of the price variable on the customer loyalty variable is 0.498, so that variable is said to have a direct influence on customer loyalty. The results of the fifth hypothesis indicate that the trust variable affects the customer loyalty variable as much as 28.3% with a sig level. 0.000 which is small from the standard coefficient of 0.05, it can be said that the trust variable has a direct influence on customer loyalty. The biggest variable that influences customer loyalty towards purchasing airline tickets and booking hotel boldly on Traveloka is the price variable because customers feel that the price that comes out of the customer is based on the benefits obtained and the affordability of the price.